1996
DOI: 10.1046/j.1526-4610.1996.3605335.x
|View full text |Cite
|
Sign up to set email alerts
|

Migraine Headache Following Stellate Ganglion Block for Reflex Sympathetic Dystrophy

Abstract: The alteration of extracranial blood flow in conjunction with clinical signs of autonomic nervous system dysfunction have led to various explanations concerning the pathophysiology of migraine headache.Reflex sympathetic dystrophy, a painful disorder of the sympathetic nervous system, can be treated by blocking the sympathetic nerves located in the stellate ganglion, resulting in vasodilation, ptosis, miosis, and anhydrosis. In theory, these changes could trigger a migraine headache attack secondary to autonom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 6 publications
1
9
0
Order By: Relevance
“…In addition, several of our cases have “spells” which resemble dysautonomic crises including irritability, headache, pallor, syncope, and clonic movements with a normal EEG. Migraine headache is not usually considered to be a symptom of dysautonomia, although it is not uncommon in Riley‐Day [Personal communication Sonia Peltzer, M.D., President, Familial Dysautonomia Hope, Inc.], and neurovascular dysautonomia has been proposed as a potential cause of migraine [Cortelli, 1993; Lehmann et al, 1996]. As previously stated, abnormal autonomic function has been reported in two series of children with CVS, and has been considered to be part of its cause and/or pathogenesis [Rashed et al, 1999; To et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several of our cases have “spells” which resemble dysautonomic crises including irritability, headache, pallor, syncope, and clonic movements with a normal EEG. Migraine headache is not usually considered to be a symptom of dysautonomia, although it is not uncommon in Riley‐Day [Personal communication Sonia Peltzer, M.D., President, Familial Dysautonomia Hope, Inc.], and neurovascular dysautonomia has been proposed as a potential cause of migraine [Cortelli, 1993; Lehmann et al, 1996]. As previously stated, abnormal autonomic function has been reported in two series of children with CVS, and has been considered to be part of its cause and/or pathogenesis [Rashed et al, 1999; To et al, 1999].…”
Section: Discussionmentioning
confidence: 99%
“…The second case was that of a 59-yearold man who developed dystonia and complex regional pain syndrome type 1 after receiving high doses of ergotamine for migraine treatment. 10,11 Our case is distinct from these cases as it is a child who was already diagnosed with a case of migraine on prophylaxis who developed complex regional pain syndrome type 1 unrelated to therapy. A few recent studies in adults have now concluded that migraine can be a risk factor for complex regional pain syndrome type 1 and the presence of migraine can be associated with a more severe form of complex regional pain syndrome type 1.…”
Section: Discussionmentioning
confidence: 87%
“…We only found one other report describing this phenomenon in a patient, with a previous history of meningitis [1]. But how did the cervicothoracic block trigger the headache in a patient without neurological or vascular disorders?…”
mentioning
confidence: 88%